Effect of Service Quality and Customer Statisfaction on Customer Loyality in Regional VII Indonesia Telecommunication Company Makassar - Suaeb, M. Irwan (Patria Artha University, 2018)
The purpose of this study is 1) To determine and analyze the effect of service quality on customer loyalty in the Indonesian Regional VII Makassar Telecommunications company, and 2) To find out and analyze the effect of customer satisfaction on customer loyalty in the Makassar Indonesia Regional VII Makassar company. The analytical method used in this study is a multiple regression analysis method. The research data was obtained from the customers of the Indonesian Regional VII Makassar Telecommunications. The research approach is an explanatory causal approach. The results showed that 1) Based on the results of multiple regression tests, the effect of service quality variables had a positive and significant effect on customer loyalty in the Makassar Indonesia Regional VII Makassar company. This means that the better the quality of services provided, the higher the customer loyalty, and 2) Based on the results of multiple regression tests, the effect of customer satisfaction variables has a positive and significant effect on customer loyalty in the Makassar Indonesia Regional VII Makassar company. This means that the better customer satisfaction is given, the higher the customer loyalty